1994
DOI: 10.1111/j.1365-2672.1994.tb03051.x
|View full text |Cite
|
Sign up to set email alerts
|

Visible light damage to Escherichia coli in seawater: oxidative stress hypothesis

Abstract: The effect of visible light on Escherichia coli H10407 in seawater microcosms was investigated. Light damage was estimated by loss of colony-forming ability. Illumination of E. coli suspended in oligotrophic seawater with visible light at an intensity of about 40 klux caused a drastic decrease of culturable bacteria which turned to a viable but non-culturable state. In seawater E. coli exhibited weak metabolic activity as estimated by 3H methyl-thymidine incorporation in the cell. Visible light did not signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
65
0
5

Year Published

2000
2000
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(77 citation statements)
references
References 35 publications
5
65
0
5
Order By: Relevance
“…The most harmful effect was found when bacteria behavior was analyzed according to the culturability pattern. The effect of sunlight on culturability has been reported by numerous authors in both fresh water and seawater [16]. Barcina et al [1] concluded that one of the effects of visible radiation on Escherichia coli cells in fresh water is the progressive loss of their capacity to multiply in standard bacteriological media.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most harmful effect was found when bacteria behavior was analyzed according to the culturability pattern. The effect of sunlight on culturability has been reported by numerous authors in both fresh water and seawater [16]. Barcina et al [1] concluded that one of the effects of visible radiation on Escherichia coli cells in fresh water is the progressive loss of their capacity to multiply in standard bacteriological media.…”
Section: Discussionmentioning
confidence: 99%
“…A number of factors induce the VBNC state, including starvation, which is probably the most predominant factor for most of the bacteria studied [15,20,28,33], temperature [32], NaCl concentration [30,33] and visible light [8,16]. The conditions shown to induce nonculturability differ according to the organism [24].…”
Section: Introductionmentioning
confidence: 99%
“…Cells have at their disposition enzymes (superoxidase, peroxydases etc.) which reduce or trap radicals such as β-carotene (Gourmelon et al, 1994;Ochsner et al, 2000). When nutrient concentrations (organic matter essentially) are not sufficient, the global cell metabolism can be reduced and cell development can be stopped.…”
Section: Influence Of Atmospheric Chemistry On the Viability Of Airbomentioning
confidence: 99%
“…photodynamic treatment) has been reported in the literature (Wilson, 1994;Henry et al, 1995Henry et al, , 1996Konig et al, 2000;Soukos et al, 2005), and it has been suggested that this effect is mediated through the production of ROS (Gourmelon et al, 1994). This hypothesis is further supported by the observation that obligate anaerobic oral bacteria (pigmented and non-pigmented) are more susceptible to blue light exposure treatment than facultative ones (Feuerstein et al, 2004;Sterer & Feuerstein, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…It was further suggested that light-induced production of reactive oxygen species (ROS) is the mechanism underlying this phototoxic effect (Gourmelon et al, 1994). The aim of the present study was to test the hypothesis that zinc may promote the phototoxic effect of high-intensity blue light against malodour-producing bacteria in an experimental model of oral biofilm.…”
Section: Introductionmentioning
confidence: 99%